Melanosis Coli: A Helpful Contrast Effect or a Harmful Pigmentation?. (December 2018) - Abu Baker, Fadi; Mari, Amir; Feldman, Dan; Suki, Muhammad; Gal, Oren; Kopelman, Yael
Background: Melanosis coli, a brown discoloration of colonic mucosa, is considered as a benign condition mainly observed in patients under chronic anthranoid laxatives. Recent data link this condition with an increased adenoma detection rate. Moreover, its tumorigenic potential and possible association with the development of colorectal cancer remains uncertain. We conducted this study to compare the polyp detection rate and colorectal cancer diagnosis in patients with melanosis against matched control group without melanosis. Patients and methods: A retrospective single-center study. Patients diagnosed with melanosis coli on colonoscopy over a 15-year period were included. Each melanosis coli patient was matched with three controls by age, gender, setting (inpatient/outpatient), and procedure's indication. Polyp detection rate and diagnosis of colorectal cancer were recorded and compared between the groups before and after adjustment for bowel preparation. Results: A cohort of 718 patients with melanosis and 2154 controls were included. The polyp detection rates were 33.4% and 21.8% of melanosis and control groups, respectively ( P < .001). Melanosis coli, however, was associated with less diagnosis of colorectal cancer than controls (0.3% vs 3.9%; P < .001). In multivariate analysis, melanosis diagnosis on endoscopy was significantly associated with higher polyp detection rate (odds ratio [OR] = 1.986, 95% confidence interval [CI]: 1.626-2.425; P value < .01). Conclusions: Melanosis coli is not associated with increased diagnosis of colorectal cancer. It is associated, however, with enhanced polyp detection likely due to chromo-endoscopy-like effect.